Direct electronetting of high-performance membranes based on self-assembled 2D nanoarchitectured networks - Shichao Zhang (Nature Portfolio, 2019)
Nanofibrous networks are applied in environmental protection and electrical or bioengineering and experience a great demand, but the design of these functional materials is challenging. Here the authors demonstrate an electronetting technology for fabricating self-assembled nanonets from various materials.